Semantic programming for AI and Robotics - Goncharov, Sergey; Nechesov, Andrey (2022 IEEE International Multi-Conference on Engineering, Computer and Information Sciences (SIBIRCON), 2022)
The paper presents a new high-level object-oriented programming language L ∗ which is a conservative extension of the p-complete logical programming language L. The p-complete language L was developed by us earlier within the framework of semantic programming theory based on PAG-theorem, p-iterative and conditional terms. Thus, L ∗ -programs can be used to implement any algorithms of polynomial complexity in such areas as artificial intelligence, robotics and smart contracts. This is especially true of the so-called explainable artificial intelligence (or briefly XAI), where it is necessary not only to give out the result based on the obtained data, but also to explain this result in a human-understandable language. This requires a programming language based on the basic constructions of mathematical logic such as logical formulas and terms. Moreover, the syntax of language L ∗ is as close as possible to the most popular programming languages such as C++, PHP, JavaScript. Which provides programmers with a quick entry into development.